Services liberalization in the Philippines a capacity needs assessment for AEC 2015 - Aldaba, Rafaelita M.; Aldaba, Fernando T. (2012)
The paper aims to assess and determine the capacity-building needs required to liberalize trade in services in the Philippines. Through the ASEAN Framework Agreement on Services, the Philippines has committed to liberalize various sectors including air transport, maritime transport, construction, financial services, and telecommunications. The overall progress of services liberalization has been modest compared to trade in goods due mainly to constitutional restrictions, limitations on market access, and application of the national treatment principle. Apart from these constitutional and legal constraints, the other obstacles to services liberalization include high cost of doing business, inadequate infrastructure, and governance issues affecting the competitiveness of industries, among others.

Clear gaps in the capacity of national agencies and regulators to effectively implement the country`s services liberalization commitments exist. To address these, the paper suggests capacity building and technical assistance as part of a comprehensive trade strategy covering both goods and services, formulating roadmaps for the various services sectors, and enhancing current coordination mechanisms among government agencies, private sector, and civil society.
Keywords: Service industries; Southeast Asia -- Economic integration